Juan Ruiz, Libro de buen amor. Ed. de José Luis Girón Alconchel. Castalia, Madrid, 1985; 366 pp. (Castalia didáctica, 8). - Delmar, Fernando (El Colegio de México, 1985)
Se reseñó el libro: Libro de buen amor.